2014
DOI: 10.1128/ec.00054-14
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformans Dual GDP-Mannose Transporters and Their Role in Biology and Virulence

Abstract: dCryptococcus neoformans is an opportunistic yeast responsible for lethal meningoencephalitis in humans. This pathogen elaborates a polysaccharide capsule, which is its major virulence factor. Mannose constitutes over one-half of the capsule mass and is also extensively utilized in cell wall synthesis and in glycosylation of proteins and lipids. The activated mannose donor for most biosynthetic reactions, GDP-mannose, is made in the cytosol, although it is primarily consumed in secretory organelles. This compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 63 publications
2
30
0
Order By: Relevance
“…While FLAG has been used in C . neoformans by others [ 54 , 55 ], we could find no record of the nuceloplasmin NLS being employed; perhaps it is this element that is toxic. We cannot be certain which of these explanations, if any, are the reason for the differences in this work and that published for C .…”
Section: Discussionmentioning
confidence: 67%
“…While FLAG has been used in C . neoformans by others [ 54 , 55 ], we could find no record of the nuceloplasmin NLS being employed; perhaps it is this element that is toxic. We cannot be certain which of these explanations, if any, are the reason for the differences in this work and that published for C .…”
Section: Discussionmentioning
confidence: 67%
“…To determine if Yap1 was required for virulence of C. neoformans , we utilized a mouse inhalation model of infection (32) to compare infection isogenic wild-type C. neoformans (K99α:wt) and two independent yap1 Δ derivatives. No significant difference in the virulence of the yap1 Δ strains compared to wild-type could be seen as P values for the difference between wild-type and either independent yap1 Δ strain were >0.01.…”
Section: Resultsmentioning
confidence: 99%
“…C. neoformans strains were tested for virulence as described previously (32) using a mouse inhalation model. Isogenic wild-type (KN99α) and two yap1 Δ ::G418 R derivatives were grown overnight in rich medium and washed in phosphate-buffered saline.…”
Section: Methodsmentioning
confidence: 99%
“…In the course of this work, we generated a rich resource for systems biology of fungal virulence. We increased the number of publically available RNA-seq profiles from C. neoformans TF-deletion studies 20-fold, more than doubled the total number of Cryptococcus expression profiles (including microarrays), presented the first time course of expression during capsule induction, and generated virulence- (Cottrell et al 2007;Wang et al 2014), and Ugt1 is a UDP-Gal transporter (Moyrand et al 2007); transporters for the other precursors have not been identified. (B) Network-derived regulatory relationships between the TFs shown in A, using the same colors and symbols except that TFs are circles.…”
Section: Discussionmentioning
confidence: 99%